Penerapan Model Pembelajaran Pair Checks untuk Meningkatkan Kemampuan Kerja Sama Siswa pada Tema Daerah Tempat Tinggalku Kelas IV Sekolah Dasar Negeri 014 Sungai Keranji - Isvadila Dila; Herlina -; Syarifuddin - (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to determine the improvement of students' cooperative abilities on the theme of the area where I live through the application of thelearning model pair checks Grade IV State Elementary School 014 Sungai Keranji. This research is motivated by the lack of student collaboration skills because there are still many students who do not help each other in group learning. This research is a classroom action research. The subjects of this study were 1 teacher and 20 students in grade IV of the State Elementary School 014 Sungai Keranji. While the object is the application of thelearning model pair checks and students' collaboration skills. This research was conducted in two cycles and each cycle consisted of two meetings. Data collection techniques using observation and documentation techniques. While the data analysis technique used is descriptive qualitative analysis with percentages. Based on the results of research and data analysis shows that thelearning model pair checks can improve students' cooperative abilities. This can be seen from before the action only reached 43.42% with the Less category. After doing the class action in the first cycle, the students' cooperation ability increased to 70.28% in the Good category. While in the second cycle there was an increase to 90% in the Very Good category. Thus, it can be concluded that the application of thelearning model pair checks can improve students' collaboration skills on the theme of the area where I live in class IV of the 014 Sungai Keranji State Elementary School.